How to become a successful invasive tapeworm: a case study of abandoned sexuality and exceptional chromosome diversification in the triploid carp parasite Atractolytocestus huronensis Anthony, 1958 (Caryophyllidea: Lytocestidae) - Špakulová, Marta; Bombarová, Marta; Miklisová, Dana; Nechybová, Stanislava; Langrová, Iva (Parasites & vectors, 2019)
BACKGROUND: A cytogenetic analysis of the new local triploid population of the caryophyllidean tapeworm Atractolytocestus huronensis, a unique parthenogenetic species with the ability to colonise new regions, was performed to understand the inner structure of its chromosome complement. METHODS: A karyotype analysis was carried out using classical Giemsa staining and C-banding combined with fluorescent DAPI staining. A hypothesis that triplets are composed from three homologue chromosomes of approximately the same length and same centromere position was tested statistically for multiple dependent variables using a non-parametric Friedman's ANOVA. The chromosomal location of ribosomal DNA clusters within the nucleolar organization region (NORs) and telomeric (TTAGGG)n sequences were detected by fluorescent in situ hybridization (FISH). Chromosomes were subjected to AgNO3 staining in order to determine whether the rDNA sites represent active NORs. RESULTS: The cytogenetic analysis confirmed the karyotype composed from eight chromosome triplets (3n = 24) as well as the existence of a pair of NORs located on each chromosome of the second triplet. Six NORs varied their activity from cell to cell, and it was reflected in the numbers of nucleoli (from 1 to 5). A huge morphological diversification of homologue chromosomes was originally detected in six out of eight triplets; the homologue elements differed significantly either in length and/or morphology, and some of them carried discernible interstitial telomeric sequences (ITSs), while the end telomeres were minute. The heterochromatin bands with high AT content varied irregularly, and the course of aberrant spermatogenesis was evident. CONCLUSIONS: Diversification of homologues is a unique phenomenon very likely caused by the long-term absence of a recombination and consequential accumulation of chromosome rearrangements in the genome of A. huronensis during species evolution. Unalterable asexual reproduction of the tapeworm, along with international trade in its host (carp), is facilitating its ongoing spread.
Keywords: Cestoda; Male; Fish Diseases; chromozomy; karyotypizace; Reproduction; triploidie; Aberrant meiosis; Karyotyping; kapři; mužské pohlaví; rozmnožování; Interstitial telomere sequences (ITSs); Animals; spermatocyty; Spermatocytes; ženské pohlaví; Chromosomes; zvířata; nemoci ryb; Diversification of homologues; Carps; Polyploidy; Triploidy; Female